(untitled) - Reece, Norine C (Tokyo,Rutland, Vt., 1958)
This volume gives an illuminating and comprehensive account of the nature and history of the cultured pearl. Covered are history of the tremendous efforts.
Keywords: Cultured pearls,Nuôi cấy ngọc trai,Pearl industry and trade,Ngành công nghiệp ngọc trai và thương mại; Japan,Nhật Bản